2007
DOI: 10.1093/eurpub/ckm051
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviours as explanations for educational level differences in cardiovascular and all-cause mortality: a follow-up of 60 000 men and women over 23 years

Abstract: Smoking, low vegetable use and physical inactivity explained a substantial part of educational level differences in cardiovascular and all-cause mortality among men and women. Socioeconomic trends in these behaviours are of crucial importance in determining whether socioeconomic mortality differences will widen or narrow in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
201
5
15

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(237 citation statements)
references
References 28 publications
15
201
5
15
Order By: Relevance
“…We found lower SRH in patients with a lower education level. The level of education can be connected with unhealthy behaviour, as shown in other studies (24). Associations of lower education and economic status on the self-assessment of health and negative prediction of chronic diseases on the self-rating of health were also found in other studies (25,26).…”
Section: Interpretation Of the Study Resultssupporting
confidence: 67%
“…We found lower SRH in patients with a lower education level. The level of education can be connected with unhealthy behaviour, as shown in other studies (24). Associations of lower education and economic status on the self-assessment of health and negative prediction of chronic diseases on the self-rating of health were also found in other studies (25,26).…”
Section: Interpretation Of the Study Resultssupporting
confidence: 67%
“…Several prospective and cross-sectional studies in different countries have reported the inverse association of social class with cardiovascular morbidity and mortality independent of conventional risk factors or access to health care, and this association was also found in countries with universal healthcare systems, as in our country [8][9][10][11].…”
Section: Discussionsupporting
confidence: 66%
“…People are likely to underestimate unhealthy health behavior, such as cigarette smoking [16], or alcohol abuse as self-estimated [17]. It has been shown that the main reasons for nonresponse in self-reported surveys are probably the predisposing sociodemographic and behavioral factors [18,19]: nonrespondents are more likely to represent the low socioeconomic status and have more unhealthy behaviors than respondents. The time between the HBS and the CRC screening invitation was more than 10 years for 84% of the study population, and health behavior-related factors may have changed in these individuals during this period.…”
Section: Discussionmentioning
confidence: 99%